COASTAL AND MARINE ENVIRONMENT PROBLEMS IN EAST KALIMANTAN PROVINCE - Supriharyono . (JOURNAL OF COASTAL DEVELOPMENT, 2000)
Coastal and marine problems were collected from the coastal community in area of the Municipality of Balikpapan East Kalimantan Province, from fishermen, NGO’s and government officials. The technique used was that of the Field Participatory Workshop’s. the result of the study revealed some coastal community awarenees, coastal resources usage, and governmental policy. The local government’s failure to solve those problems was mainly due to lack of social awarenees for environmental coastal management and lack enforcement.